Catalytic hydrogenolysis of lignin to phenolic monomers over Ru supported N,S-co-doped biochar: The importance of doping atmosphere - Gao, Wenran; Wang, Ke; Wu, Yishuang; Zhu, Xun; Wu, Yinlong; Zhang, Shoujun; Li, Bin; Huang, Yong; Zhang, Shu; Zhang, Hong (Frontiers in Chemistry, 2022)
Doping of heteroatoms into carbon materials is a popular method to modify their physicochemical structures and has been widely used in the fields of energy conversion and storage. This study aims to investigate the effect of doping atmosphere on the catalytic performance of nitrogen and sulfur co-doped biochar supported Ru in the production of phenolic monomers from lignin hydrogenolysis. The results showed that the catalyst prepared under CO2 atmosphere (Ru@CNS-CO2) was able to produce phenolic monomers from corncob lignin with a yield up to 36.41 wt%, which was significantly higher than that from the run over N2-prepared catalyst (Ru@CNS-N2). The characterization of the catalysts demonstrated that the CNS-CO2 support had a larger specific surface area, richer C=S and C-S groups, and higher oxygen content than CNS-N2, resulting in finer Ru particles and more Ru0 content on the CNS-CO2 support. The Ru@CNS-CO2 catalyst exhibited high activity in hydrogenation and fragmentation of β-O-4 linkages.